Coastal forms and deposits in Bulgarian Antarctic Base area, Livingston Island - Kenderova, R.; Pimpirev, Ch.; Baltakova, A.; Pristavova, S. (Ukrainian Antarctic Journal, 2012)
Bulgarian Antarctic Base (S62o38’25.7’’ W60o21’54.9’’, 13 m a.s.l.) is located in the South Bay of Livingston Island, South Shetland archipelago. The coast line has length of 1.8 km and it contains alternate sections with predominate abrasion or accumulation processes. This study comments the results of geomorphological and sedimentological investigations of deposits, which build the accumulative form complex: high and low marine terrace, pebble beach and at some places moraines. In abrasion areas are developed bench and cliff with niches, which are described only.